2012
DOI: 10.1021/ic2019132
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine Coordination to a Cobalt Diimine–Dioxime Catalyst Increases Stability during Light-Driven H2 Production

Abstract: The combination of cobalt diimine-dioxime complexes with a cyclometalated iridium photosensitizer gives efficient systems for hydrogen generation under visible-light irradiation using triethylamine as a sacrificial electron donor. Interestingly, the addition of triphenylphosphine (PPh(3)) to the medium results in a significant improvement of the stability of the system, with up to ∼700 turnovers achieved within 10 h. UV-visible spectroscopic monitoring of the reaction allows identification of a PPh(3)-coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 36 publications
4
79
2
1
Order By: Relevance
“…Although the exact role of the phosphine ligand could not be elucidated by the authors, mechanistic investigations showed that during catalysis, phosphine is coordinated to the iron centre to produce a [Fe 3 (CO) 11 PR 3 ] complex as well as a second unidentified phosphine complex. A similar effect was observed for a cobalt diimine dioxime water reduction catalyst, which exhibits a two-fold activity upon addition of PPh 3 (Zhang et al 2012). In this case, coordination of the phosphine to the photogenerated Co(I) species, which is assumed to be the initiating species in the hydrogen evolution catalytic cycle, was confirmed.…”
Section: Multicomponent Systems For Light-driven Water Reductionsupporting
confidence: 74%
“…Although the exact role of the phosphine ligand could not be elucidated by the authors, mechanistic investigations showed that during catalysis, phosphine is coordinated to the iron centre to produce a [Fe 3 (CO) 11 PR 3 ] complex as well as a second unidentified phosphine complex. A similar effect was observed for a cobalt diimine dioxime water reduction catalyst, which exhibits a two-fold activity upon addition of PPh 3 (Zhang et al 2012). In this case, coordination of the phosphine to the photogenerated Co(I) species, which is assumed to be the initiating species in the hydrogen evolution catalytic cycle, was confirmed.…”
Section: Multicomponent Systems For Light-driven Water Reductionsupporting
confidence: 74%
“…This family of complexes has become of renewed interest in the past few years, following reports in 2005 [1,2] and 2007 [3,4,5] of their promising hydrogen-evolving catalytic capability. Today, cobaloximes, and the related diimine-dioxime cobalt complexes [6,7,8,9], are recognized as some of the most efficient molecular catalysts for electro-and photo-catalytic hydrogen evolution [10,11,12]. These compounds are known to be powerful nucleophiles in their reduced Co(I) state.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, the spectroscopic signatures of Co(I) intermediates have been observed during the course of electro-and photo-catalytic experiments [4,5,22], and the Co(I) species [14,23,24,9], and its protonated Co(III)-H form [25,26,27], have been isolated and characterized in a few, rare cases. In this context, we recently examined the sole hydridocobaloxime isolated to date, [HCo(dmgH) 2 (PnBu 3 )] [26], using a mixture of experiment and theory [25].…”
Section: Introductionmentioning
confidence: 99%
“…2, P6a, ppy = 2-phenylpyridine) and TEA as the reducing agent (development of iridium photosensitizers was performed prior to this work and will be discussed later in this Perspective). 94 Irradiation of this system produced 307 TON Co in 4 hours. It was determined that catalyst decomposition was responsible for the termination of hydrogen evolution, which quickly led to PS destruction.…”
Section: Macrocyclic Cobalt Complexesmentioning
confidence: 99%